JPEG raw [compact disc] - Clark, Gary, Jr., 1984- (Warner Records, 2024)
Gary Clark Jr.'s fourth studio release marks a grand step in his musical elevation. A powerful and expansive artistic statement. While retaining the deep and true resonance of his blues foundations and guitar virtuosity with subtlety yet conviction, he reaches well beyond this time.